Characterization of Tunneling Nanotubes in Wharton's jelly Mesenchymal Stem Cells : An Intercellular Exchange of Components between Neighboring Cells - Sanchez, Viviana (2017)
Intercellular communication is one of the most important events in cell population behavior. In the last decade, tunneling nanotubes (TNTs) have been recognized as a new form of long distance intercellular connection. TNT function is to allow molecular and subcellular structure exchange between neighboring cells via the transfer of molecules and organelles such as calcium ions, prions, viral and bacterial pathogens, small lysosomes and mitochondria. New findings support the concept that mesenchymal stem cells (MSCs) can affect cell microenvironment by the release of soluble factors or the transfer of cellular components to neighboring cells, in a way which significantly contributes to cell regulation and tissue repair, although the underlying mechanisms remain poorly understood. MSCs have many advantages for their implementation in regenerative medicine. The TNTs in these cell types are heterogeneous in both structure and function, probably due to their highly dynamic behavior. In this work we report an extensive and detailed description of types, structure, components, dynamics and functionality of the TNTs bridging neighboring human umbilical cord MSCs obtained from Wharton"s jelly. Characterization studies were carried out through phase contrast, fluorescence, electron microscopy and time lapse images with the aim of describing cells suitable for an eventual regenerative medicine.